Evaluating the Role of Self-Esteem on Differential Career Outcomes by Gender in Academic Medicine. (October 2020) - Manne-Goehler, Jennifer; Freund, Karen M.; Raj, Anita; Kaplan, Samantha E.; Terrin, Norma; Breeze, Janis L.; Carr, Phyllis L.
Abstract : Purpose: Gender differences in faculty advancement persist in academic medicine. Understanding of what drives these differences remains limited. The relationship among self-esteem, gender, and career outcomes has not previously been explored. Method: The authors evaluated the association between gender and 2012–2013 career outcomes, specifically, the number of publications, academic rank, leadership positions, and retention, and whether self-esteem as measured in the 1995 National Faculty Survey mediates this relationship. They measured self-esteem using the modified Rosenberg Self-Esteem Scale. The authors used multivariable logistic regression analysis to understand the association among gender, self-esteem, and the outcomes of rank, leadership, and retention, and negative binomial models for number of publications. Models were adjusted for race, specialty, effort distribution, and years since first faculty appointment. The authors performed a mediation analysis to understand whether self-esteem mediates the relationship between gender and these career outcomes. Results: Overall, self-esteem scores were high. Women had lower self-esteem in 1995 than their male colleagues. In adjusted models, female gender was associated with lower performance on all 4 career outcome metrics. While self-esteem scores were positively associated with all 4 outcomes, the authors' mediation analysis suggested that self-esteem did not mediate the relationship between gender and these 4 career metrics. Conclusions: Female medical faculty members lag behind men on traditional metrics of faculty achievement. While higher self-esteem is positively associated with faculty achievement, it did not mediate the relationship between gender and career advancement over the 17 years of follow-up and, thus, may not be an ideal target for programs and policies to increase gender parity in academic medicine.